Black Ash - a Forgotten Domestication Trait in Garden Orach (Atriplex hortensis L.) - Lutz Zwiebel (EXARC Journal)
Do folktale heroines tell of a prehistoric plant ash use? The culinary use of plant ash is an ancient technology nearly extinct worldwide and completely absent from Eurasian cultural history. Despite the lack of this technology´s historical documentation, folktales provide a rich yet underestimated corpus on salt and ash. The denotation of the physical substances as well as the related narrative structures are investigated throughout several tale types. Motifs and their typical transformations show a wide distribution accompanied by a common collective understanding. Origin and loss of such plant ash tradition are linked to prehistory. The expression of gender specific education in fundamentally changed social contexts is hypothesized. Vladimir Propp´s structural analysis is introduced as a tool elucidating unconscious human heritage.